THE EFFECT OF DISTRIBUTION COST, DISTRIBUTION CHANNELS AND MARKETING CHANNELS ON THE SALES VOLUME OF MIE SEDAAP ON PT. ADR WING GROUP LHOKSEUMAWE CITY - Muhammad Rizki; Adnan (RADJA PUBLIKA, 2023)
This study aims to determine how the effect of distribution costs, distribution channels, and marketing channels on the sales volume of Mie Sedaap at PT. ADR Wings Group in Lhokseumawe City. The data used in this study was primary data by distributing questionnaires to 90 respondents. The data analysis technique used in this study is multiple linear regression analysis consisting of data instrument tests, classical assumption tests, and hypothesis testing using SPSS software version 26. The results showed that distribution costs, distribution channels, and marketing channels had a positive and significant effect on the sales volume of Mie Sedaap at PT. ADR Wings Group in Lhokseumawe City.